Globalization, Migration and Class Struggles: NGO Mobilization for Filipino Domestic Workers - Lisa, Law; Kathy, Nadeu (Kasarinlan: Philippine Journal of Third World Studies; Vol 14 No 3 (1999): Politics and Governance, 2009)
This paper contributes to post-Marxist discussions on the relevance of class as a social category in a postmodern world. Rather than marginalize this issue of social positioning, the authors explore the relevance of an Althusserian perspective which acknowledges the importance of class as it articulates with other social/identity issues such as gender and ethnicity. The substantive context for this discussion is gendered labor migration from the Philippines, and the advocacy work conducted by Filipino non-government organizations (NGOs) working with migrants in Pacific Rim countries. It focuses on NGOs in Hong Kong and Vancouver, and their efforts to contest the gendered national identities which are being constructed as poor women migrate to wealthier countries to seek employment as domestic workers. These contexts highlight the articulation of issues of class, gender and ethnicity in conceptualizing the migration of Filipino women, and the authors argue that NGO activities provide insights on how to envision decentered class struggles in relation to transnational migration.